2017
DOI: 10.1073/pnas.1718806115
|View full text |Cite
|
Sign up to set email alerts
|

Structural and molecular basis of mismatch correction and ribavirin excision from coronavirus RNA

Abstract: Coronaviruses (CoVs) stand out among RNA viruses because of their unusually large genomes (∼30 kb) associated with low mutation rates. CoVs code for nsp14, a bifunctional enzyme carrying RNA cap guanine N7-methyltransferase (MTase) and 3'-5' exoribonuclease (ExoN) activities. ExoN excises nucleotide mismatches at the RNA 3'-end in vitro, and its inactivation in vivo jeopardizes viral genetic stability. Here, we demonstrate for severe acute respiratory syndrome (SARS)-CoV an RNA synthesis and proofreading pathw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

30
582
5
7

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 379 publications
(624 citation statements)
references
References 63 publications
(108 reference statements)
30
582
5
7
Order By: Relevance
“…An open question that warrants further investigation is the role of the 3Ј-5Ј exonuclease (nsp14) in susceptibility to RDV. It has previously been reported that nucleotide analog inhibitors can be excised by the viral exonuclease (14). A murine hepatitis virus mutant lacking the 3Ј-5Ј exonuclease activity was shown to be more sensitive to RDV (5).…”
Section: Editors' Pick: Coronavirus Polymerase Inhibition With Remdesmentioning
confidence: 99%
See 1 more Smart Citation
“…An open question that warrants further investigation is the role of the 3Ј-5Ј exonuclease (nsp14) in susceptibility to RDV. It has previously been reported that nucleotide analog inhibitors can be excised by the viral exonuclease (14). A murine hepatitis virus mutant lacking the 3Ј-5Ј exonuclease activity was shown to be more sensitive to RDV (5).…”
Section: Editors' Pick: Coronavirus Polymerase Inhibition With Remdesmentioning
confidence: 99%
“…Progress has also been made in characterizing the SARS-CoV RdRp complex (13)(14)(15). Biochemical data suggest that the active complex is composed of at least three viral nonstructural proteins nsp7, nsp8, and nsp12.…”
mentioning
confidence: 99%
“…ATAi sa na nionic polymer shown to bind to a variety of protein targets, including gp120o fH IV-1 and HIV-2, that has been demonstrated to prevent SARS-CoV replication (IC 50 = 0.2 mg mL À1 ). [32,34] In order to develop nucleoside analogues to effectively inhibit viral RNA replication, the nucleoside must either evade detection by the exonuclease or must outcompete exonuclease activity.R emdesivir (GS-5734) is an excellent example of the latter.A na denosine analogue prodrug with a1 '-nitrile, it displayed potent efficacy against SARS and MERS in human airway epithelial (HAE) cell models and in mice (IC 50 = 0.069 and 0.074 mm for SARS-CoV and MERS-CoV,r espectively,i nH AE). [28] Beyond this exception,t he remainingR dRp inhibitors have been nucleoside analogues,a nd these provide the most promisinga venue towards disrupting viral RNA replication.…”
Section: Rna-dependent Rna Polymerasementioning
confidence: 99%
“…Development of nucleoside analogue inhibitors of CoVs is further hampered by the novel RNA-dependent RNA proofreading activity of CoV nonstructural protein 14, a 3 0 to 5 0 exoribonuclease (nsp14-ExoN), which confers up to 20-fold increase in replication fidelity compared with other RNA viruses. The nsp14-ExoN activity is responsible for native CoV high resistance to many nucleoside analogues including ribavirin and 5-fluorouracil [11][12][13]. Nevertheless, the recent development of nucleotide and nucleoside analogue inhibitors with a high barrier for resistance, broad-spectrum activity against multiple CoVs, and the ability to inhibit WT CoVs in the presence of nsp14-ExoN holds promise for the treatment of CoV disease.…”
Section: Cov Antiviral Strategiesmentioning
confidence: 99%